Peran Mahkamah Pidana Internasional (ICC) Dalam Penegakan Hukum Pidana Internasional Terhadap Kejahatan Genosida - Shiva, Khadizah Aliyah; Rahmawati, Tri; Salsabilla, Nashwa; Putry, Salsabila Afifany Susanta; Mulia, Risma; Saleh, Weldy Jevis (Universitas Pahlawan Tuanku Tambusai, 2025)
International law is continually evolving to keep pace with changes in the global community. This progress has led to the creation of the International Criminal Court, which is associated with the United Nations. Formed under the UN's leadership, this court addresses the pressing need for justice related to the gravest offenses. The primary aim of the International Criminal Court is to remove any safeguards that individuals who commit significant human rights abuses have previously enjoyed, and to assist in thwarting the most severe violations of human rights according to international criminal law, thus encouraging global accountability. The International Criminal Court (ICC) stands as a permanent and autonomous judicial entity that acts as a criminal tribunal. Founded by the United Nations and rooted in the Rome Statute instituted in 1998, the ICC is empowered to investigate, prosecute, and penalize individuals, regardless of their official status within their nations.